Letter to the Editor about the article published in Clinical Oral Investigations tilted “Impacted and transmigrated mandibular canines: an analysis of 3D radiographic imaging data” (Bertl MH, Frey C, Bertl K, Giannis K, Gahleitner A, Strbac GD (2018), Clin Oral Investig, doi: 10.1007/s00784-018-2342-0) - Paweł Plakwicz; Krzysztof Kukuła (Clinical Oral Investigations, 2018)
Changes in the oral mucosa are characteristic of snus-induced lesions (SILs), typically occurring at the site of pouch placement. These lesions are reversible after cessation. This study evaluated the effects of two non-tobacco-based nicotine pouches (ZYN® Dry and ZYN® Moist) on SIL severity, salivary cytokines, epithelial thickness, and inflammatory cell presence after 28 days of exclusive use. In this open-label, randomized longitudinal study, 45 daily snus users were assigned to either the dry formulation (n = 23) or the moist formulation (n = 22) for four weeks. Clinical assessments were performed at baseline, day 14, and day 28. Lesions were graded on a four-point scale. Biopsies and saliva samples were collected at baseline and day 28. Both groups showed significant improvement in lesion severity (p < 0.0001). No significant changes were observed in epithelial thickness, inflammatory cell infiltration, total protein levels, IL-1β, TNF-α, or MCP-1. IL-8 levels increased significantly in the dry formulation group (p < 0.01). Switching to nicotine pouches improved SILs without major changes in the inflammatory markers assessed. Nicotine pouches were associated with improvement of snus-induced lesions in this study population. ISRCTN13243849, registered 01/09/2022.